Komunikasi Politik Islam di Era Digital : Kajian terhadap Strategi Partai Islam dalam Pemilu - Ahmad Muhamad Mustain Nasoha; Ashfiya Nur Atqiya; Ria Aulia; Alifa Anis Nur Anjani; Fanany Laila Muqsitin (Mahkamah : Jurnal Riset Ilmu Hukum, 2025)
This study explores the political communication strategies of Islamic parties in facing elections during the digital era in Indonesia. Using a qualitative normative approach, the research focuses on literature analysis, regulatory review, and interpretation of relevant legal documents. Findings show that Islamic parties actively utilize social media platforms such as Instagram, Facebook, Twitter, and YouTube, along with official websites and digital applications to deliver political messages. Their communication strategies integrate religious messages with social, economic, and national issues, adopting a moderate and inclusive narrative to attract young, digitally active voters.Collaboration with influencers, religious leaders, and online communities also plays a significant role in expanding their outreach. However, challenges remain, including unequal technology access in rural areas, low digital literacy among certain groups, and the threat of disinformation that could damage political reputations. Additionally, digital campaign regulations in Indonesia are still inadequate.The study concludes that the success of Islamic political communication in the digital era depends on the ability to manage digital identity, engage with online communities, and respond adaptively to emerging issues. It recommends strengthening party cadres’ digital capacities, improving public digital literacy, and enhancing regulatory frameworks to support a more inclusive and democratic political participation.